2015
DOI: 10.1093/eurheartj/ehv254
|View full text |Cite
|
Sign up to set email alerts
|

Changes in ventricular remodelling and clinical status during the year following a single administration of stromal cell-derived factor-1 non-viral gene therapy in chronic ischaemic heart failure patients: the STOP-HF randomized Phase II trial

Abstract: BackgroundStromal cell-derived factor-1 (SDF-1) promotes tissue repair through mechanisms of cell survival, endogenous stem cell recruitment, and vasculogenesis. Stromal Cell-Derived Factor-1 Plasmid Treatment for Patients with Heart Failure (STOP-HF) is a Phase II, double-blind, randomized, placebo-controlled trial to evaluate safety and efficacy of a single treatment of plasmid stromal cell-derived factor-1 (pSDF-1) delivered via endomyocardial injection to patients with ischaemic heart failure (IHF).Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
91
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(92 citation statements)
references
References 34 publications
1
91
0
Order By: Relevance
“…98, 99 In a PHASE 2 study, 93 HFrEF patients with ischemic disease received intramyocardial injection of a single treatment of 15 or 30 mg of plasmid SDF-1 (pSDF-1) or placebo. 100 Although a primary composite endpoint was not met, there was a trend towards improved EF with pSDF-1. Patients in the lowest EF tertile who received 30 mg of drug demonstrated significant placebo adjusted changes in EF after 12 months.…”
Section: Gene Transfer (Gt) Therapymentioning
confidence: 96%
“…98, 99 In a PHASE 2 study, 93 HFrEF patients with ischemic disease received intramyocardial injection of a single treatment of 15 or 30 mg of plasmid SDF-1 (pSDF-1) or placebo. 100 Although a primary composite endpoint was not met, there was a trend towards improved EF with pSDF-1. Patients in the lowest EF tertile who received 30 mg of drug demonstrated significant placebo adjusted changes in EF after 12 months.…”
Section: Gene Transfer (Gt) Therapymentioning
confidence: 96%
“…The crucial role of SDF-1 for cardiac repair in chronic ischemic heart failure was the reason for conducting clinical trial using SDF-1 nonviral gene therapy via its endomyocardial administration [99]. This blinded placebo-controlled STOP-HF trial demonstrated improvement of clinical status based on composite endpoint of six MWD (6-min walk distance) and MLWHFQ (Minnesota Living with Heart Failure Quality of life Questionnaire).…”
Section: Sdf-1 As a Key Regulator Of Vessel Developmentmentioning
confidence: 99%
“…In response to chronic ischemia stimuli, cardiac fibroblasts proliferate, migrate, and excrete ECM to maintain myocardial function. However, if the repair phase is not terminated appropriately, excessive deposition of ECM will result in chronic fibrosis, ultimately leading to worse cardiac function and a poor prognosis [6][7][8] . During the development of cardiac remodeling after myocardial infarction, the proliferation and migration of cardiac fibroblasts play critical roles in heart failure.…”
Section: Introductionmentioning
confidence: 99%